2021
DOI: 10.1002/cphc.202100341
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Conjugated Structure on the Magnesium Storage Performance of Dianhydrides

Abstract: Inorganic cathodes of rechargeable Mg batteries suffer from limited selections, while organic materials provide more options. Herein, three conjugated dianhydrides, pyromellitic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride and 3,4,9,10-perylenetetracarboxylic dianhydride are comparatively investigated to elucidate the effects of conjugated structure on the Mg 2 + storage performances. It is observed that the reversible Mg 2 + storage capacity is more dependent on the conjugated structure than ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…P26 showed a higher capacity than N14 and N26 despite the larger unit formula weight and lower theoretical capacity. This is consistent with our previous report 39 stating that the larger conjugated structure of PTCDA effectively delocalizes the electron density and enhances the carbonyl enolization.…”
Section: Resultssupporting
confidence: 94%
“…P26 showed a higher capacity than N14 and N26 despite the larger unit formula weight and lower theoretical capacity. This is consistent with our previous report 39 stating that the larger conjugated structure of PTCDA effectively delocalizes the electron density and enhances the carbonyl enolization.…”
Section: Resultssupporting
confidence: 94%
“…To further investigate the effect of the conjugated structures of organic compounds on the performance of magnesium batteries, three different degrees of conjugated acid anhydrides were selected. [65] Surprisingly, 3,4,9,10-perylenetetracarboxylic dianhydride with larger conjugated facets displayed higher Mg 2 + storage capacity and better cycling stability in practice, which was the opposite of the theoretical capacity (Figure 10b). Ex-situ X-ray photoelectron spectroscopy (XPS) analysis demonstrated that the large conjugated structure of PTCDA enhanced the carbonyl enolization and played a more important role in the reversible storage capacity of Mg 2 + .…”
Section: Carbonyl Compoundsmentioning
confidence: 88%
“…To further investigate the effect of the conjugated structures of organic compounds on the performance of magnesium batteries, three different degrees of conjugated acid anhydrides were selected [65] . Surprisingly, 3,4,9,10‐perylenetetracarboxylic dianhydride with larger conjugated facets displayed higher Mg 2+ storage capacity and better cycling stability in practice, which was the opposite of the theoretical capacity (Figure 10b).…”
Section: Oems In Smbsmentioning
confidence: 99%
“…Studies have shown that the expansion of conjugated structure would be beneficial for the charge transport and hence the rate capability (Figure 6a). [56][57][58] The molecular design to improve conductivity will be further discussed below.…”
Section: Rational Molecular Designmentioning
confidence: 99%